2017
DOI: 10.11646/phytotaxa.331.2.7
|View full text |Cite
|
Sign up to set email alerts
|

Pinus vallartensis (Pinaceae), a new species from western Jalisco, Mexico

Abstract: We propose and describe Pinus vallartensis Pérez de la Rosa & Gernandt as a new species from western Jalisco, Mexico. The pine occurs near the southern limit of the Sierra Occidental at the intersection of the municipalities of Puerto Vallarta, Cabo Corrientes, and Talpa de Allende. Pinus oocarpa occurs within the margins of this forest to the south and P. jaliscana to the west. The more distantly related pine, P. maximinoi, also grows in the area. Pinus vallartensis is like P. jaliscana and P. oocarpa in poss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 6 publications
0
2
0
1
Order By: Relevance
“…However, the macro and microscopic differences could cause them to be classified as different taxa. Considering that Humaria is an ectomychorrizal genus (Tedersoo et al, 2006;Erős-Honti et al, 2008) and the country has a high diversity of ecosystems, being the home of 161 species of Quercus (Valencia-A, 2004) and 50 of Pinus (Gernandt and Pérez-de la Rosa, 2014;Pérez-de la Rosa and Gernandt, 2017), we believe that a comprehensive review of the genus is needed. It is imperative that morphological and phylogenetic studies of other collections identified as Humaria hemisphaerica be carried out, as well as their ecology.…”
Section: Discussionmentioning
confidence: 99%
“…However, the macro and microscopic differences could cause them to be classified as different taxa. Considering that Humaria is an ectomychorrizal genus (Tedersoo et al, 2006;Erős-Honti et al, 2008) and the country has a high diversity of ecosystems, being the home of 161 species of Quercus (Valencia-A, 2004) and 50 of Pinus (Gernandt and Pérez-de la Rosa, 2014;Pérez-de la Rosa and Gernandt, 2017), we believe that a comprehensive review of the genus is needed. It is imperative that morphological and phylogenetic studies of other collections identified as Humaria hemisphaerica be carried out, as well as their ecology.…”
Section: Discussionmentioning
confidence: 99%
“…With M. vallartensis, it is recommended to decree a protection zone in the Palo María stream basin, since it is one of its main distribution sites in addition to having other endemic species such as Pinus vallartensis Pérez de la Rosa & Gernandt [126] and Miconia vallartensis Zabalgoitia, Figueroa & Muñiz-Castro [127], which would contribute significantly to the conservation of Puerto Vallarta's biodiversity. In this particular case, the importance of establishing a protection zone and rescuing this species also rests on the fact that this species was declared an emblematic tree of the Municipality from which it bears its name, Puerto Vallarta.…”
Section: Reintroductionmentioning
confidence: 99%
“…En México varias de las especies del género Pinus L. están representadas por poblaciones pequeñas y dispersas (Ledig et al, 2001). De las 50 especies reportadas (Gernandt y Pérez de la Rosa, 2013; Pérez de la Rosa y Gernandt, 2017), 11 se encuentran en alguna categoría de riesgo en la Lista Roja de la Unión Internacional para la Conservación de la Naturaleza (IUCN, 2021), siendo en su mayoría especies del subgénero Strobus L., subsección Cembroides Engelm.…”
Section: Introductionunclassified